Acute social defeat does not alter cerebral 5‐HT2A receptor binding in male Wistar rats. Issue 9 (23rd May 2014) - Visser, Anniek K.D.; Meerlo, Peter; Ettrup, Anders; Knudsen, Gitte M.; Bosker, Fokko J.; den Boer, Johan A.; Dierckx, Rudi A.J.O.; van Waarde, Aren
ABSTRACT It has been hypothesized that effects of uncontrollable stress on serotonin receptor expression contribute to the etiology of stress‐related disorders like depression. While the serotonin‐2A receptors (5‐HT2AR) are thought to be important in this context, only few studies examined effects of stress on this receptor subtype. In this study, we therefore assessed acute and long‐term changes in 5HT2AR binding after social defeat stress in rats. Male Wistar rats were subjected to social defeat by placing them in the home cage of an aggressive, dominant Long Evans rat. Acute social defeat suppressed growth, but did not affect anxiety‐like behavior in an open field test. A positron emission tomography scan with the 5‐HT2AR tracer [11C]MDL 100907 1 day and 3 weeks after defeat did not show significant changes in receptor binding. To verify these results, [3H]MDL 100907 binding assays were performed in homogenates of prefrontal cortex and hippocampus, which also did not indicate any changes in Bmax or Kd. These findings do not support the hypothesis that changes in 5‐HT2AR function are a vital mechanism through which uncontrollable stress contributes to stress‐related pathologies such as depression. It remains to be determined whether effects of stress on 5HT2AR binding depend on the nature of the stressor or on the characteristics of the rat strain. Synapse, 2014. © 2014 Wiley Periodicals, Inc.